Impact of diabetes on dengue – a comparative study of clinical and inflammatory variables in patients with and without diabetes - Jafri, Asif Dabeer; Dhar, Srikant Kumar; Maiti, Sourav; Janardhanan S., Aparna; Dash, Abhijit; Rizvi, Kayenaat; Verma, Alka (European Journal of Clinical and Experimental Medicine, 2025)
Introduction and aim. Dengue fever is a mosquito-borne viral disease and its severity may be influenced by comorbid conditions such as diabetes mellitus, which can alter the inflammatory and clinical response. This study aimed to evaluate and compare clinical characteristics, laboratory findings, and inflammatory markers between patients with and without diabetes who were diagnosed with dengue infection. Material and methods. The retrospective observational study included 100 patients with confirmed dengue infection, divided equally into 50 with diabetes and 50 without. It examined the distribution of age, HbA1C levels, clinical symptoms, bleeding events, liver enzymes, and inflammatory markers. Correlation analyzes were conducted to assess the relationship between HbA1C levels and inflammatory markers within each group. In addition, inflammatory markers were compared in different age categories (<50 years and ≥50 years) and by diabetic status. Results. Laboratory findings, including liver enzymes and inflammatory markers, were markedly elevated in the diabetic cohort (p<0.001). The correlation analysis revealed a strong positive relationship between HbA1c and inflammatory markers in the diabetic group (r>0.8, p<0.001), while weaker correlations were observed in the non-diabetic group (r=0.4–0.6, p<0.001). Inflammatory markers were significantly higher in diabetic patients, particularly those 50 and older. Conclusion. Diabetes may contribute to a more intense inflammatory response in dengue, highlighting it as an independent risk factor for severe clinical outcomes in dengue infection.